Prevalence of potential drug interactions among outpatients' prescriptions of community pharmacies in Nineveh Governorate, Iraq - Hala F. Kasim (GarVal Editorial Ltda., 2023)
Context: Management of chronic diseases requires the use of various drugs and dietary supplements. Their use is a potential source of drug interactions that interfere with therapeutic responses. Aims: To determine the prevalence of potential drug interactions, severity levels, and related risk factors in outpatient prescriptions submitted to community pharmacies. Methods: A cross-sectional study was conducted using convenience sampling. From August to December 2021, outpatient prescription data were collected from 16 community pharmacies within the Nineveh Governorate-Iraq. Recorded data included age (≥18 years), gender, and prescribed drugs and/or dietary supplements. Two online software programs were used for assessing drug interactions: Medscape.com and Drugs.com. Potential drug interactions were classified as minor, moderate/significant, or major/serious. Results: Among the 1000 prescriptions, the total interactions were 1373. More than half of the prescriptions (57.6%, 576/1000) had potential drug interactions. These interactions were mainly observed among the drugs (89.9%, 518/576). The severity of the interactions was mostly (50%) moderate/significant. A significant association (p£0.001) was reported for numerous prescribed items with the occurrence of potential interactions. Nonsteroidal anti-inflammatory drugs/aspirin (44%), and calcium/magnesium-containing products (approximately 20%) contributed to the most frequent potential drug interactions. Conclusions: A high prevalence of potential drug interactions, mostly of moderate severity, was reported among outpatient prescriptions. These interactions are significantly associated with the number of prescribed items. The vital role of pharmacists in adopting strategies for monitoring potential drug interactions is essential for ensuring safe therapeutic regimens for patients.